A Trend Factor for the Cross Section of Cryptocurrency Returns - Fieberg, Christian; Liedtke, Gerrit; Poddig, Thorsten; Walker, Thomas; Zaremba, Adam (Journal of Financial and Quantitative Analysis, 2025)
Abstract We propose CTREND, a new trend factor for cryptocurrency returns, which aggregates price and volume information across different time horizons. Using data on more than 3,000 coins, we employ machine learning methods to exploit information from various technical indicators. The resulting signal reliably predicts cryptocurrency returns. The effect cannot be subsumed by known factors and remains robust across different subperiods, market states, and alternative research designs. Moreover, it survives the impact of transaction costs and persists in big and liquid coins. Finally, an asset pricing model that incorporates CTREND outperforms competing factor models, providing a superior explanation of cryptocurrency returns.